Effects of Fracture Formation Stage on Shale Gas Preservation Conditions and Enrichment in Complex Structural Areas in the Southern Sichuan Basin, China - Li, Jing; Li, Hu; Xu, Jianliang; Wu, Yijia; Gao, Zhi (Frontiers in Earth Science, 2022)
Fractures have significantly impacted the preservation, enrichment, and productivity of shale gas in the Longmaxi Formation in the complex structural area of the southern Sichuan Basin. Based on outcrop, core, imaging logging, inclusion analysis, acoustic emission experiments, and burial and thermal evolution history data, the formation stage, evolution and preservation conditions of structural fractures were comprehensively studied. Shear fractures are the main features of tectonic origin and are characterized by small widths, wide spacing, and high filling degrees. The structural fractures of the Longmaxi Formation can be divided into three groups in terms of their formation stage. The first-stage fractures were formed in the middle-late period of the Yanshanian tectonic movement (86.2-68.5 Ma), when the palaeotectonic stress was 68.33-71.82 MPa; and the homogenization temperature of the fluid inclusions in the corresponding fracture fillings is 150-178 ℃. The second-stage fractures were formed at the end of the Yanshanian -early Himalayan tectonic movement (68.5-35.2 Ma), when the palaeotectonic stress was 85.2-100.5 MPa; the homogenization temperature of the corresponding fluid inclusions is 123-148 ℃. The third-stage tectonic fractures formed during the middle-late period of the Himalayan tectonic movement (35.2-0 Ma), when the palaeotectonic stress was 55.6-63.8 MPa; fillings are scarce in these fractures, but the measured homogenization temperature of the corresponding fluid inclusions is 90-110℃. Shale gas preservation conditions were affected by the fracture formation stage, maximum horizontal crustal stress, fault scale, structural burial depth, formation pressure coefficient, etc. Three types of favourable preservation conditions were identified. The Type I target area is the low slope area in the middle of the syncline, which occurs more than 2.0 km from the fault. The research results have guiding significance for the evaluation of the preservation conditions of deep shale gas in the study area and similar areas.